2020
DOI: 10.1002/chem.202000530
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Photochromic Molecules Based on Dihydroazulene Units

Abstract: Multi-photochromic systemsi ncorporating individually addressables witching units are attractivef or development of advanced data storaged evices.H ere, we present the synthesis and properties of as election of such molecular systemsi ncorporating the dihydroazulene/vinylheptafulvene (DHA/VHF) photo-/thermoswitch. The influence of the linker (meta-phenylene vs. azulene-1,3-diyl vs. thiophene-2,5-diyl) separating two DHA units on the switching properties was investigated. An azulene-1,3-diyl spacer largely inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Addition of a Cu I salt to VHF−Ph was previously found to shorten the VHF half‐life from 545 to approximately 20 min in CH 2 Cl 2 at 25 °C due to complexation of the CN groups [1k,13] . Addition of Cu I to a solution of meta‐ VHF‐ c AZB‐VHF did indeed accelerate the TBR and allowed detection of two different rate constants, but Cu I seemed to perturb also the AZB isomerization, and we could not access selectively meta ‐DHA‐ c AZB‐DHA in this way.…”
Section: Resultsmentioning
confidence: 82%
“…Addition of a Cu I salt to VHF−Ph was previously found to shorten the VHF half‐life from 545 to approximately 20 min in CH 2 Cl 2 at 25 °C due to complexation of the CN groups [1k,13] . Addition of Cu I to a solution of meta‐ VHF‐ c AZB‐VHF did indeed accelerate the TBR and allowed detection of two different rate constants, but Cu I seemed to perturb also the AZB isomerization, and we could not access selectively meta ‐DHA‐ c AZB‐DHA in this way.…”
Section: Resultsmentioning
confidence: 82%
“…Molecules 2021, 26, x FOR PEER REVIEW 4 of 13 some degradation as well (Figure 1, bottom box) [29]. This "meta-rule" of photoactivity of phenylene-bridged photoswitch dimers was also established for azobenzenes [31,32], and is an important general design criterium.…”
Section: Synthesis Of Ortho-substituted Dha-ph's 1-4mentioning
confidence: 69%
“…The para-connected bridge separates the two DHA units by a linearly conjugated pathway, and the compound exhibits a redshifted absorption maximum in comparison to DHA-Ph and to the cross-conjugated meta-phenylene-bridged DHA dimer. Changes in the bridging unit from phenylene to thiophene-2,5-diyl ("para-like" connectivity, linear conjugation) or to azulene-1,3-diyl ("meta-like" connectivity, cross-conjugation) further confirmed that cross-conjugation allows sequential switchings, while linear conjugation reduces the photoactivity considerably, with full photoisomerization to VHF-VHF being accompanied by some degradation as well (Figure 1, bottom box) [29]. This "meta-rule" of photoactivity of phenylene-bridged photoswitch dimers was also established for azobenzenes [31,32], and is an important general design criterium.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations